Právo, psychologie a zneužívání alkoholu (aktuální právně aplikační a psychologické otázky) - Černý, Michal; Brzobohatá, Karin, 1967-; Masarykova univerzita. Katedra právní teorie (2007)
Práce se zabývá zneužíváním alkoholu a zejména právními a psychologickými aspekty tohoto palčivého společenského problému. Práce je rozdělena na teoretickou a praktickou část, která se zejména zaměřuje na problematiku zneužívání alkoholu v brněnské oblasti.
Within the frame of my diploma thesis I researched the dilemma of an abuse of alcoholic bevareges, addiction to them and also healing alcoholism as a desease. First, I compared a consumption of alcoholic bevareges with other psychoactive drugs evaluation of their danger to health and society. Theoretical part of my diploma thesis is ended with historical review of misusage of alcohol bevareges and also legal point of view to different cultures in different times. Practical part is focused to the region of city Brno, forms of abuse of alcohol and subsequent strugle to alcoholism.
Vedoucí práce: Karin Brzobohatá.
Diplomová práce (Mgr.)--Masarykova univerzita, Právnická fakulta, 2007.
Keywords: alkoholismus; právo; alcoholism; law; diplomové práce